Cultural competencies for nurses : impact on health and illness - Dayer-Berenson, Linda (Jones&Barlett, 2011)
This Text Is A Resource To Help The Nurse At All Levels Navigate Through The Obstacles That Culture Can Place On The Patient Experience. It Compiles The History And Theory Behind Cultural Competency In Nursing And Offers Key Information Regarding Health Beliefs And The Impact Of Culture On Health And Illness